Narrative explorations of the micro-politics of students' citizenship, belonging and alienation at South African universities - Carolissen, R.; Kiguwa, P. (South African Journal of Higher Education, 2018)
Citizenship and social justice have been explored from ethical and theoretical perspectives in education. Furthermore, alienation or belonging in institutional cultures, often invoking social locations such as gender and race, were explored. Little research, especially empirical research, exists at the nexus of narrative, citizenship, belonging and subjectivities. In contexts of ongoing inequalities and associated student protests, legacies of unequal histories come into conflict in the crucible of higher education. Narrative as theory-method may usefully provide ways in which citizenship and identity may be connected to socio-historical processes and justice in higher education. Narratives of student experiences have the potential to provide insight into the nuances of subjectivities in personal and collective stories of belonging and alienation. They may also highlight how universities can be spaces where students may engage in non-normative negotiations and reconstructions of subjectivities to create different narratives about themselves and public spaces, thus signalling change.